The unsolved role of heightened connectivity from the unaffected hemisphere to paretic arm muscles in chronic stroke. Issue 5 (May 2019) - Hammerbeck, Ulrike; Hoad, Damon; Greenwood, Richard; Rothwell, John C.
Highlights: Corticospinal connections from the unaffected hemisphere are strengthened after stroke. Ipsilateral corticospinal connectivity is not correlated to functional ability. The functional role of increased ipsilateral connectivity after stroke remains unclear. Abstract: Objective: Ipsilateral connectivity from the non-stroke hemisphere to paretic arm muscles appears to play little role in functional recovery, which instead depends on contralateral connectivity from the stroke hemisphere. Yet the incidence of ipsilateral projections in stroke survivors is often reported to be higher than normal. We tested this directly using a sensitive measure of connectivity to proximal arm muscles. Method: TMS of the stroke and non-stroke motor cortex evoked responses in pre-activated triceps and deltoid muscles of 17 stroke survivors attending reaching training. Connectivity was defined as a clear MEP or a short-latency silent period in ongoing EMG in ≥ 50% of stimulations. We measured reaching accuracy at baseline, improvement after training and upper limb Fugl-Meyer (F-M) score. Results: Incidence of ipsilateral connections to triceps (47%) and deltoid (58%) was high, but unrelated to baseline reaching accuracy and F-M scores. Instead, these were related to contralateral connectivity from the stroke hemisphere. Absolute but not proportional improvement after training was greater in patients with ipsilateral responses. Conclusions: Despite enhanced ipsilateral connectivity, arm function and learning was related most strongly to contralateral pathway integrity from the stroke hemisphere. Significance: Further work is needed to decipher the role of ipsilateral connections.